Research in ActionSerendipity and Children's Literature Research in the Library. Issue 2 (December 2016) - Kidd, Kenneth; Pearson, Lucy; Pyke, Sarah
Abstract : Serendipity has become a ' sine qua non of archival research' (Tamboukou 151), but it is less clear how it might be cultivated – or even whether such a pursuit is worthwhile. Newcastle University's 2015 masterclass on the place of the archive within children's literature research offered the opportunity to explore the role of serendipity from several perspectives, exposing both the possibilities and the limitations of serendipity in the archive. Paradoxically, serendipity is best fostered by sustained scholarly enquiry, but it also depends on a willingness to move beyond a focus on specific outcomes. This raises questions about the future of serendipitous research in an academic world which allows increasingly little time for exploratory research and about the impact of new technologies.